Penerapan Akuntansi pada Usaha Mikro, Kecil, dan Menengah (UMKM) ( Studi pada UMKM Raja Eskrim ) di Kota Kediri - Sayekti Indah Kusumawardhany (Jurnal Akuntansi dan Perpajakan, 2020)
The Central Statistics Agency noted that in 2018, SMES in Indonesia had reached 64.2 million units by contributing 60% of gross domestic product (GDP). This will have a positive impact in increasing the country's economic growth. In general, SMES in Kediri do not use an accounting system in managing funds. This study will take the object of SMES in Kediri in the food and beverage industry, the name is  Raja Eskrim. This study aims to find out how the application of accounting at SMES and to find out perceptions about the importance of applying accounting in business activities. This study uses a qualitative approach to the type of phenomenological research. Data was collected using the interview method and the interview process was carried out using systematic questions that the researchers had compiled in accordance with the research objectives. The results of this study indicate that at the SMES Raja Eskrim conduct accounting applications with simple records, but do not always make financial reports due to limited time and knowledge by financial statement makers. In addition to making simple accounting records, Raja Eskrim SMES also take notes for planning and sales targets. From the interview results, the owner has the perception that the application of accounting is very important because the owner receives benefits that can apply for KUR and determine the steps in the future. DOI: 10.26905/ap.v6i2.4570